The Effect of Education Based on the Theory of Planned Behavior on Preventive Behaviors of Vaginitis in Health Ambassadors - Elaheh Mokarrami; Zahra Jalili; Hamid Tavakoli Ghouchani (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: one of the most common genital tract infections among women is vaginitis. It is a very serious issue due to its potential side effects for women. The aim of this study is to determine the effect of education based on the Theory of Planned Behavior, on preventive behaviors of vaginitis among Health Ambassadors in Maneh and Samalghan County. Methods: A semi-experimental interventional study was conducted using random sampling method among 80 health ambassadors in reproductive age of 18-49 years of selected comprehensive health centers in the city. Data gathering tool was a questionnaire designed based on the theory of planned behavior, the validity and reliability of which had been approved prior to the study and before and after educational intervention was completed by intervention and control groups. The data were analyzed by SPSS 19 and using the statistical tests Kolmogorov Smirnov, Chi-square, T-test, Mann-Whitney. Results: The results showed that the mean age of women was 30.86 ± 6.6 and the mean age of marriage was 18.24 ± 4.1. After the educational intervention, The mean score of knowledge, constructs of the theory of planned behavior (attitude, subjective norms, perceived behavioral control and behavioral intention), and vaginitis preventive behavior Increased in the intervention group significantly compared to the control group (P<0.001) Conclusion: The health education program designed based on the theory of planned behavior was effective in Promoting preventive behaviors of Vaginitis.